Stability and electrochemical performance of nanostructured La2CuO4þd cathodes - Dos-Santos-Gómez, Lucía; Porras-Vázquez, José Manuel; Hurtado, Javier; Losilla, Enrique R.; Marrero-López, David (Elsevier, 2019)
La2CuO4þd cathode layers are prepared by spray-pyrolysis deposition and their structural, microstructural and electrical properties are compared with those of submicrometric powders obtained from freeze-dried precursors. In order to improve the cathode performance, three different electrode architectures have been proposed: (i) powder cathodes obtained by conventional screen-printing and sintering, and cathodes deposited by spray-pyrolysis on: (ii) as-prepared electrolyte surfaces and (iii) porous electrolyte backbones. The cathode activity for the oxygen reduction reaction has been investigated as a function of the microstructure and the sintering temperature. The microstructural optimization of the cathodes and the low fabrication temperature minimize the instability problems between the electrolyte and the cathode materials, leading to polarization resistances as low as 0.14 U cm2 at 600 C.
Keywords: Pilas de combustible; Microelectrodos; Ce0.9Gd0.1O2-d; La2CuO4; Nanostructured electrodes; Solid oxide fuel cells